Clinical outcome of elderly patients with unresectable pancreatic cancer treated with gemcitabine plus S-1, S-1 alone, or gemcitabine alone: Subgroup analysis of a randomised phase III trial, GEST study. (February 2016) - Imaoka, Hiroshi; Kou, Tadayuki; Tanaka, Masao; Egawa, Shinichi; Mizuno, Nobumasa; Hijioka, Susumu; Hara, Kazuo; Yazumi, Shujiro; Shimizu, Yasuhiro; Yamao, Kenji
Abstract: Background: In the GEST study of unresectable pancreatic cancer, S-1 demonstrated non-inferiority compared to gemcitabine, but gemcitabine plus S-1 (GS) did not show superiority over gemcitabine for overall survival (OS). We performed subgroup analysis of these data focused on the efficacy and safety of these regimens as a first-line treatment for elderly patients. Methods: Elderly patients (≥70 years, n = 261) treated for unresectable pancreatic cancer (GS: n = 90, S-1: n = 85 and gemcitabine: n = 86) were analysed. Results: No significant differences between the GS, S-1, or gemcitabine groups in OS (median: 10.2, 8.0 and 8.5 months, respectively) or objective response rates (27.6%, 25.3% and 14.3%, respectively) were noted. Grade ≥III adverse haematological events were observed more frequently in GS-treated than in S-1- or gemcitabine-treated elderly patients (p < 0.001 and p = 0.016, respectively). Four of 8 patients aged ≥80 years experienced serious adverse events. Conclusions: S-1 and gemcitabine are both efficacious options for treatment of elderly patients with unresectable pancreatic cancer. Conversely, first-line treatment of elderly patients with GS should only be used after careful consideration. Highlights: We performed a subgroup analysis from a randomised phase III trial, the GEST study. Gemcitabine plus S-1 (GS), S-1, and gemcitabine treatment resulted in similar overall survival. Severe adverse haematological events were more frequent with GS treatment. Three treatment-related deaths were observed in elderly GS-treated patients.